Tinjauan Yuridis Terhadap Pembatalan Akta Wasiat Dalam Sengketa Warisan: Studi Putusan Nomor 211/pdt.G/2020/PN Jkt.Pst - Rayi Kharisma Rajib; Fadhil Citra Darmakusuma; Muhammad Afrizal Habibi (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
A will deed as an authentic deed has binding legal force; however, in practice, it may be annulled if it contradicts legal provisions and harms the rights of heirs. This study aims to analyze the judge’s legal considerations in the annulment of a will deed in inheritance disputes based on Decision Number 211/Pdt.G/2020/PN Jkt.Pst and its legal consequences for the parties involved. This research uses a normative legal research method with statutory and case approaches. The results show that the annulment of the will deed was based on legal defects causing the will to fail to meet the validity requirements regulated in the Indonesian Civil Code, including the protection of the compulsory portion rights of heirs (legitieme portie). The legal consequence of such annulment is that the will deed loses its binding legal force, and the distribution of inheritance reverts to inheritance provisions under statutory law. This study is expected to serve as a reference for notaries and the public in drafting will deeds in accordance with applicable legal provisions.